Behavior In Preventing Children With Pneumonia In Kamonji Community Health Center, Subdistrict West Palu, Palu City - Kurniawan, Herman; Raramiranda, Raramiranda; Napirah, Muh. Ryman (Preventif : Jurnal Kesehatan Masyarakat, 2020)
Pneumonia is an acute infection that attacks lung tissue (alveoli) caused by bacteria, virus and fungi. According to WHO, in 2015 pneumonia accounted for 16% of all children deaths under-five years and killed 920.136 toddlers. The number of cases of under-five pneumonia in Indonesia in 2012 was 549.708 cases. While, in 2013 there was 571.547 cases. Kamonji Health Center is the health center which has the highest incidence of pneumonia in Palu, amounted to 536 cases of patients from 2,508 cases. The aim of the study is to find out the knowledge and attitudes of mothers, facilities and health services, family and health workers support for mothers who have pneumonia at Kamonji Health Center. The research used was qualitative using indepth interview as data collection techniques. The subject of the study were 9 informants who were determined by purposive sampling technique. The results show that maternal knowledge is still lack due to the less of information which mother gets about pneumonia. Mother's attitude regarding the incidence of pneumonia shows a positive attitude. Health facilities and health workers at the Kamonji Health Center are already good. Likewise with family support that is already good enough. Suggestions for the Kamonji Health Center are expected to provide counseling to the toddlers' mothers and families as informants in preventing pneumonia.